Block-Chain Based Unified Identity Authentication System in Medical Report for Health-Cares - Waheed , Mohammed Abdul; Ansari, Najma Shaheen; Begum , Zohara (International Journal of Membrane Science and Technology, 2023)
Organisations and individuals can efficiently manage their identity management operations with the help of identity management software. 'Identity Management' (IdM) software assists the administrators of an organisation in clearly defining and modifying a person's role in the organisation and authorising the relevant access to them. An identity management process is designed to identify, authenticate, and authorise individuals to access organisational software resources. Using this programme, administrators are also able to monitor user login and activity on the corporate computer network. Thus, operational security is improved. The healthcare industry has grown at the quickest rate in terms of revenue and data. Security is now more crucial than ever because electronic medical records are so common. The security of each patient's medical records is a top priority in current medical systems. Furthermore, there are efforts to increase safety of this confidential data by encrypting it. Therefore, we advocated for implementation of block chain systems as decentralized approach to protecting patients' health information. It has three parts: data retrieval, encryption, and authentication using block chain technology. While assuring patient protection, the suggested framework might also keep the healthcare system's security and legitimacy.